Skema Proses Pra Produksi pada Film Dokumenter Camp Vietnam - Sandi Prasetyaningsih (Politeknik Negeri Batam, 2014)
The Documenterary film is one of multimedia products where is can used as media in order to telling information. Usually, documentary film take shoots in real location, without actor and focus on the subjects, such as history, science, social or environment. The basic objective are to enlighten, to provide information, eduation, persuasion and provide knowledge about surrounding environment. The documentary film combines two ascpects of human real life, science aspect and art. Science aspect and art contained in documentary film is a explanation about facts arranged in a part in order to have artisti c values and make audience can understand what actually happened. Batam island is a archipelago that has several small island arounded. One of the is Galang Island which is a witness to history of human tragedy of Vietnamses refugees. In this area built a settlement called Vietnamese Camo as an agreement between the United Nations High Commissioner for Refugees (UNHCR) and the Indonesian government.